Bromate electroreduction in acidic solution inside rectangular channel under flow-through porous electrode conditions - Vorotyntsev, Mikhail A.; Antipov, Anatoly E. (Electrochimica acta, 2019)
In view of applied prospects of the bromate electroreduction in acidic medium this process has been analyzed for the solution flow through a channel filled in with porous conducting material playing the role of 3D electrode. The process passes via mediator redox cycle where the bromine is reduced at the electrode surface to bromide which is subject to the comproportionation reaction with bromate inside the solution phase to regenerate bromine. Inside the entering solution protons are in excess compared to bromate ions while the bromine concentration is very low. Ohmic losses across the channel are disregarded. Perpendicular size of pores is assumed to be sufficiently small so that the diffusion of solute components suppresses concentration gradients in the transversal direction. Solute species are transported along the channel by the convective mechanism. Numerical and approximate analytical methods of solving coupled transport equations have provided distributions of solute components inside the porous medium and of the current density along the flow coordinate, y. Quite unusual features of the process have been discovered, in particular non-monotonous variation of the bromine concentration and of the current density as functions of y, with narrow maxima at an intermediate distance from the entrance, dependent on the flow velocity and rate constants of the electrochemical and chemical steps of the redox cycle. All these surprising features of the bromate reduction process originate directly from the autocatalytic character of this cycle where each passage of the cycle increases the amount of the catalytic bromine/bromide couple in solution, thus accelerating the bromate transformation. As a result one can reach simultaneously both high efficiency of the bromate transformation and strong current for an optimal value of the channel length-to-flow velocity ratio, even for extremely small ratio of the incoming bromine and bromate concentrations.